EXTENSIVE LISTENING AS A TOOL FOR LANGUAGE PROFICIENCY IMPROVEMENT: A QUALITATIVE ANALYSIS OF STUDENT FEEDBACK - Rusmiati, Rusmiati; Rakhmyta, Yunie Amalia; Hanif, Hanif; Saputra, Edi (English Education Department, 2024)
A key component of learning a language is listening, which is necessary for the growth of receptive and productive language skills. Extensive Listening (EL), which involves engaging with a wide range of audio materials in the target language, has emerged as a significant pedagogical tool for enhancing listening skills. This study investigates the effectiveness of EL in improving language proficiency through a 13-week program involving three undergraduate students in an English language course. Utilizing a qualitative research design, the study explores students' perceptions of the benefits, challenges, and overall impact of EL on their English language skills. The findings indicate that students perceive EL as beneficial for vocabulary acquisition, pronunciation, and listening comprehension. However, challenges such as difficulties in finding relevant content and understanding diverse accents were also identified. The study provides valuable insights into optimizing EL programs, emphasizing the need for curated content and structured syllabi to better support learners. These results contribute to the existing literature on EL by highlighting its role in language learning and offering practical recommendations for educators to enhance instructional practices. The study underscores the importance of fostering an effective learning environment tailored to the needs and preferences of language learners. Future research is suggested to see the influence of various listening materials, the effectiveness of certain techniques, and to examine the long-term impact of EL across a broader learner demographic to further validate its effectiveness as a language acquisition tool.